NK cell defects: implication in acute myeloid leukemia - D’Silva, Selma Z.; Singh, Meenakshi; Pinto, Andrea S. (Frontiers in Immunology, 2023)
Acute Myeloid Leukemia (AML) is a complex disease with rapid progression and poor/unsatisfactory outcomes. In the past few years, the focus has been on developing newer therapies for AML; however, relapse remains a significant problem. Natural Killer cells have strong anti-tumor potential against AML. This NK-mediated cytotoxicity is often restricted by cellular defects caused by disease-associated mechanisms, which can lead to disease progression. A stark feature of AML is the low/no expression of the cognate HLA ligands for the activating and inhibitory KIR receptors, due to which these tumor cells evade NK-mediated lysis. Recently, different Natural Killer cell therapies have been implicated in treating AML, such as the adoptive NK cell transfer, Chimeric antigen receptor-modified NK (CAR-NK) cell therapy, antibodies, cytokine, and drug treatment. However, the data available is scarce, and the outcomes vary between different transplant settings and different types of leukemia. Moreover, remission achieved by some of these therapies is only for a short time. In this review, we will discuss the role of NK cell defects in AML progression, particularly the expression of different cell surface markers, the available NK cell therapies, and the results from various preclinical and clinical trials.